Review of time-resolved non-contact electrostatic force microscopy techniques with applications to ionic transport measurements - Mascaro, Aaron; Miyahara, Yoichi; Enright, Tyler; Dagdeviren, Omur E.; Grütter, Peter (Beilstein Journal of Nanotechnology, 2019)
Recently, there have been a number of variations of electrostatic force microscopy (EFM) that allow for the measurement of time-varying forces arising from phenomena such as ion transport in battery materials or charge separation in photovoltaic systems. These forces reveal information about dynamic processes happening over nanometer length scales due to the nanometer-sized probe tips used in atomic force microscopy. Here, we review in detail several time-resolved EFM techniques based on non-contact atomic force microscopy, elaborating on their specific limitations and challenges. We also introduce a new experimental technique that can resolve time-varying signals well below the oscillation period of the cantilever and compare and contrast it with those previously established.
Keywords: atomic force microscopy; electrostatic force microscopy; ionic transport; lithium ion batteries; nanotechnology

(untitled) - Nonnenmacher, M.; O’Boyle, M. P.; Wickramasinghe, H. K. (Appl. Phys. Lett., 1991)

(untitled) - Güthner, P.; Dransfeld, K. (Appl. Phys. Lett., 1992)

(untitled) - Hamers, R.; Cahill, D. G. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 1991)

(untitled) - Krauss, T. D.; Brus, L. E. (Phys. Rev. Lett., 1999)

(untitled) - Chen, L.; Cherniavskaya, O.; Shalek, A.; Brus, L. E. (Nano Lett., 2005)

(untitled) - Coffey, D. C.; Ginger, D. S. (Nat. Mater., 2006)

(untitled) - Schirmeisen, A.; Taskiran, A.; Fuchs, H.; Roling, B.; Murugavel, S.; Bracht, H.; Natrup, F. (Appl. Phys. Lett., 2004)

(untitled) - Guo, S.; Jesse, S.; Kalnaus, S.; Balke, N.; Daniel, C.; Kalinin, S. V. (J. Electrochem. Soc., 2011)

(untitled) - Reid, O. G.; Rayermann, G. E.; Coffey, D. C.; Ginger, D. S. (J. Phys. Chem. C, 2010)

(untitled) - Cox, P. A.; Glaz, M. S.; Harrison, J. S.; Peurifoy, S. R.; Coffey, D. C.; Ginger, D. S. (J. Phys. Chem. Lett., 2015)

(untitled) - Alexe, M. (Nano Lett., 2012)

(untitled) - Mascaro, A.; Wang, Z.; Hovington, P.; Miyahara, Y.; Paolella, A.; Gariepy, V.; Feng, Z.; Enright, T.; Aiken, C.; Zaghib, K.; Bevan, K. H.; Grutter, P. (Nano Lett., 2017)

(untitled) - Jesse, S.; Balke, N.; Eliseev, E.; Tselev, A.; Dudney, N. J.; Morozovska, A. N.; Kalinin, S. V. (ACS Nano, 2011)

(untitled) - Murawski, J.; Graupner, T.; Milde, P.; Raupach, R.; Zerweck-Trogisch, U.; Eng, L. M. (J. Appl. Phys., 2015)

(untitled) - Shao, G.; Glaz, M. S.; Ma, F.; Ju, H.; Ginger, D. S. (ACS Nano, 2014)

(untitled) - Collins, L.; Ahmadi, M.; Wu, T.; Hu, B.; Kalinin, S. V.; Jesse, S. (ACS Nano, 2017)

(untitled) - Fernández Garrillo, P. A.; Borowik, Ł.; Caffy, F.; Demadrille, R.; Grévin, B. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Schumacher, Z.; Spielhofer, A.; Miyahara, Y.; Grutter, P. (Appl. Phys. Lett., 2017)

(untitled) - Garrett, J. L.; Munday, J. N. (Nanotechnology, 2016)

(untitled) - Borgani, R.; Haviland, D. B. (Rev. Sci. Instrum., 2019)

Kelvin Probe Force Microscopy: From Single Charge Detection to Device Characterization - Sadewasser, S.; Glatzel, T. (Springer International Publishing, 2018)

(untitled) - Giridharagopal, R.; Rayermann, G. E.; Shao, G.; Moore, D. T.; Reid, O. G.; Tillack, A. F.; Masiello, D. J.; Ginger, D. S. (Nano Lett., 2012)

(untitled) - Dwyer, R. P.; Nathan, S. R.; Marohn, J. A. (Sci. Adv., 2017)

(untitled) - Albrecht, T. R.; Grütter, P.; Horne, D.; Rugar, D. (J. Appl. Phys., 1991)

(untitled) - Schönenberger, C.; Alvarado, S. F. (Phys. Rev. Lett., 1990)

(untitled) - Krauss, T. D.; O'Brien, S.; Brus, L. E. (J. Phys. Chem. B, 2001)

(untitled) - Bennewitz, R.; Reichling, M.; Matthias, E. (Surf. Sci., 1997)

Phase Lock Loops and Frequency Synthesis - Kroupa, V. F. (John Wiley & Sons, Ltd, 2003)

(untitled) - Ngai, K. L.; Kanert, O. (Solid State Ionics, 1992)

(untitled) - Funke, K. (Prog. Solid State Chem., 1993)

(untitled) - Woutersen, S.; Emmerichs, U.; Bakker, H. J. (Science, 1997)

(untitled) - Pfeifer, T.; Spielmann, C.; Gerber, G. (Rep. Prog. Phys., 2006)

(untitled) - Cavalieri, A. L.; Müller, N.; Uphues, T.; Yakovlev, V. S.; Baltuška, A.; Horvath, B.; Schmidt, B.; Blümel, L.; Holzwarth, R.; Hendel, S.; Drescher, M.; Kleineberg, U.; et al. (Nature, 2007)

(untitled) - Cooke, D. G.; Hegmann, F. A.; Young, E. C.; Tiedje, T. (Appl. Phys. Lett., 2006)

(untitled) - Takihara, M.; Takahashi, T.; Ujihara, T. (Appl. Phys. Lett., 2008)

(untitled) - Giessibl, F. J. (Phys. Rev. B, 1997)

Classical Mechanics - Goldstein, H. (Pearson Education India, 2011)

Proceedings of the ESA Annual Meeting on Electrostatics 2008 - Crowley, J. M. (Simple expressions for force and capacitance for a conductive sphere near a conductive wall)
http://www.electrostatics.org/images/ESA_2008_D1.pdf

(untitled) - Dyson, F. (Nature, 2004)

(untitled) - Sader, J. E.; Jarvis, S. P. (Appl. Phys. Lett., 2004)

(untitled) - Sader, J. E.; Hughes, B. D.; Huber, F.; Giessibl, F. J. (Nat. Nanotechnol., 2018)

(untitled) - Dagdeviren, O. E.; Zhou, C.; Altman, E. I.; Schwarz, U. D. (Phys. Rev. Appl., 2018)

(untitled) - Hudlet, S.; Saint Jean, M.; Guthmann, C.; Berger, J. (Eur. Phys. J. B, 1998)

(untitled) - Sader, J. E.; Borgani, R.; Gibson, C. T.; Haviland, D. B.; Higgins, M. J.; Kilpatrick, J. I.; Lu, J.; Mulvaney, P.; Shearer, C. J.; Slattery, A. D.; Thorén, P.-A.; Tran, J.; et al. (Rev. Sci. Instrum., 2016)

(untitled) - Butt, H.-J.; Cappella, B.; Kappl, M. (Surf. Sci. Rep., 2005)

(untitled) - Colchero, J.; Gil, A.; Baró, A. M. (Phys. Rev. B, 2001)

(untitled) - Schirmeisen, A.; Cross, G.; Stalder, A.; Grütter, P.; Dürig, U. (New J. Phys., 2000)

Forces in Scanning Probe Methods - Güntherodt, H. J.; Anselmetti, D.; Meyer, E. (Springer Netherlands, 1995)

(untitled) - Cochran, W. G. (Biometrics, 1954)

(untitled) - Karatay, D. U.; Harrison, J. S.; Glaz, M. S.; Giridharagopal, R.; Ginger, D. S. (Rev. Sci. Instrum., 2016)

Noncontact Atomic Force Microscopy - Weymouth, A. J.; Giessibl, F. J. (The Phantom Force, 2015)

(untitled) - Rugar, D.; Mamin, H. J.; Guethner, P. (Appl. Phys. Lett., 1989)

(untitled) - Kiracofe, D.; Kobayashi, K.; Labuda, A.; Raman, A.; Yamada, H. (Rev. Sci. Instrum., 2011)

(untitled) - Schumacher, Z.; Miyahara, Y.; Spielhofer, A.; Grutter, P. (Phys. Rev. Appl., 2016)